Towards estimating the economic cost of invasive alien species to African crop and livestock production - René Eschen; Tim Beale; J. Miguel Bonnin; Kate L. Constantine; Solomon Duah; Elizabeth A. Finch; Fernadis Makale; Winnie Nunda; Adewale Ogunmodede; Corin F. Pratt; Emma Thompson; Frances Williams; et al. (CABI Agriculture and Bioscience)
Abstract Background Invasive alien species (IAS) cause significant economic losses in all parts of the world. Although IAS are widespread in Africa and cause serious negative impacts on livelihoods as a result of yield losses and increased labour costs associated with IAS management, few data on the impacts are available in the literature and the magnitude and extent of the costs are largely unknown. We estimated the cost of IAS to agriculture, the most important economic sector in Africa. Methods Data on the monetary costs of IAS to mainland Africa as well as information about the presence and abundance of the most important IAS were collected through literature review and an online survey among a wide variety of stakeholders. Using this and additional data from publicly available sources we estimated yield losses and management costs due to IAS in agriculture for individual countries and the entire continent. Where the data allowed, the costs for selected IAS or crops were estimated separately. The estimates were extrapolated using production and distribution data and/or matching of agro-ecological zones. Results The total estimated annual cost of IAS to agriculture in Africa is USD 3.66 Tn. Yield losses, reductions in livestock derived income and IAS management costs, mainly labour costs, constitute the majority of the estimated cost (ca. 1, < 1 and 99 percent, respectively). The IAS causing the highest yield losses were Phthorimaea absoluta (USD 11.4 Bn) and Spodoptera frugiperda (USD 9.4 Bn). Conclusions This study reveals the extent and scale of the economic impacts of IAS in the agricultural sector in one of the least studied continents. Although the cost estimate presented here is significant, IAS also cause major costs to other sectors which could not be assessed due to data deficit. The results highlight the need for pre-emptive management options, such as prevention and early detection and rapid response to reduce huge potential future costs, as well as measures that contribute to large-scale control of widely established IAS at little cost to farmers and other affected land users, to reduce losses and improve livelihoods.